Analisis Pemasaran Bibit Mangga Arumanis (mangifera indica l.) Studi Kasus Desa Tino Kecamatan Tarowan Kabupaten Jeneponto - Muhammad Arifin Fattah (Universitas Muslim Maros, 2022)
In order to develop fruits and to increase their competitiveness in both local and export markets, the government is promoting agricultural development in the horticulture sector and its marketing strategy. Mango is one of the most important fruit commodities. The purpose of this study was to analyze the marketing channels and margins of mango arumanis seeds in Tino Village, Tarowan District, Jeneponto Regency. This research was conducted in Tino Village in Tarowan District, Jeneponto Regency. The research was carried out in August - September 2021. The population of this study was 105 Arumanis mango seed farmers. The technique of determining the sample is purposive sampling. The sample used in this study were 23 people. For marketing agency respondents, samples were taken using backtracking snowball sampling from farmers to final consumers, based on information from producers and traders. Analysis of the data used is descriptive qualitative analysis and marketing margins. The results of this study are that there are two marketing channels used by farmers in marketing mango arumanis seeds in Tino Village, Tarowan District, Jeneponto Regency, namely (1) Channel I: Farmers ? Wholesalers ? Consumers, (2) Channel II: Farmers ? Wholesalers ? Retailers ? Consumers. Meanwhile, the marketing margin in marketing channel I is Rp. 20,000/tree, and the marketing margin on marketing channel II is Rp. 5,000/tree and Rp. 20,000/tree.